Requirements to Enhance Financial Inclusion as a Tributary to Support the Stability of the Algerian Financial System for the Period (2010-2021) - سنوساوي , صالح (Finance and Business Economies Review, 2023)
This research document aims to show the role of financial inclusion in supporting the stability of the Algerian financial system, and it is by examining and analyzing both the indicators of financial inclusion and financial stability in Algeria, and to determine the most important orientations of the Bank of Algeria to support the stability of the financial system by improving financial inclusion. The study concluded that the Bank of Algeria should take effective measures to improve financial services and their access to all members of society, which would contribute to activating the role of financial intermediation and access to services. financial institutions and strengthen competition between financial institutions, which promotes the stability of the Algerian financial syste.